Paradigma Smart City Dalam Memanfaatkan Potensi Big Data - Sawitri, Dara (Universitas Multi Data Palembang, 2024)
Smart City is a city where the existing command center makes it easier to access information in order to provide services to the community. The services that can be provided are varied and usually involve big data technology in order to improve people's quality of life and sustainable city efficiency. Where the increase in population in smart cities will be directly proportional to the increase in demand for city services such as smart transportation systems, smart electricity networks and so on. The right big data paradigm plays an important role in encouraging infrastructure growth and encouraging innovation that makes smart cities responsive to the needs of their residents and able to optimize the standard of living of their citizens. This is due to the ability of big data which is able to analyze large amounts of data so that it can manage resources efficiently for smart cities by utilizing advanced technology to improve services, efficiency, continuity and overall quality of life. Big Data in the development of smart city infrastructure will be examined for its benefits in its implementation. By utilizing the wealth of data in big data, smart cities can gain knowledge about patterns, trends and dynamics formed from daily activities in city development. By analyzing huge data sets, governments can make decisions about which areas need improvement to address critical issues and allocate resources efficiently for smart cities.